Pediatric firearm injury epidemiology at a level 1 trauma center from 2019 to 2021: including time of the COVID-19 pandemic - Cynthia Orantes; Hei Kit Chan; Daniel Walter; Summer Chavez; Irma T. Ugalde (BMC, 2023)
Abstract Background Firearms are a leading cause of death in children. The demand for firearms increased following COVID-19 "stay-at home orders" in March 2020, resulting in record-breaking firearm sales and background checks. We aim to describe the changes in pediatric firearm-related injuries, demographics, and associated risk factors at a Level 1 trauma center in Houston before and during the COVID 19 pandemic. Results The total number of pediatric firearm-related injury cases increased during March 15th to December 31st, 2020 and 2021 compared to the same time period in 2019 (104 verses 89 verses 78). The demographic group most affected across years were males (87% in 2019 vs 82% in 2020 and 87% in 2021) between 14 and 17 years old (83% in 2019 vs 81% in 2020 and 76% in 2021). There was an increase in firearm injuries among black youth across all years (28% in 2019 vs 41% in 2020 vs 49% in 2021). Injuries in those with mental illness (10% in 2019 vs 24% in 2020 vs 17% in 2021), and injuries where the shooter was a known family member or friend (14% in 2019 vs 18% in 2020 vs. 15% in 2021), increased from 2019 to 2020. Conclusion The total number of pediatric firearm-related injuries increased during the COVID-19 pandemic compared to the previous year despite a decline in overall pediatric emergency department visits. Increases in pediatric firearm-related injuries in already vulnerable populations should prompt further hospital initiatives including counseling on safe firearm storage, implementation of processes to identify children at risk for firearm injuries, and continued research to mitigate the risk of injury and death associated with firearms in our community.